Bioinspired Polymeric Helical and Superhelical Microfibers via Microfluidic Spinning. Issue 12 (10th April 2019) - Yang, Huili; Guo, Mingyu
Abstract: The helix and superhelix play critical roles in the achievement of tissue functions. These fascinating structures have attracted increasing interest due to their potential biomimicking applications. However, continuous and controlled fabrication of these structures, especially the superhelical structures, from various polymers for different practical applications still remains a big challenge. Here, a novel and versatile microfluidic spinning strategy is presented for generation of both helical and superhelical microfibers from either hydrophilic, hydrophobic, or amphiphilic polymers. The diameter ( d  ), wavelength (λ), and amplitude (A) of these microfibers could be highly controlled. The helical microfibers show outstanding elongations and potential applications in magnetic responsive elastic microactuators. It is envisioned that these results will greatly enrich the possibility of generating new multiple‐ordered structures from various polymers for applications in different areas. Abstract : Bioinspired helical and superhelical microfibers from either hydrophilic or hydrophobic or amphiphilic polymers are controlled and continuously generated by a novel microfluidic strategy. The helical fibers show excellent stretchable and elastic character and have potential applications in magnetic‐responsive flexible actuators.